The de novo autism spectrum disorder RELN R2290C mutation reduces Reelin secretion and increases protein disulfide isomerase expression. Issue 1 (18th May 2017) - Lammert, Dawn B.; Middleton, Frank A.; Pan, Jen; Olson, Eric C.; Howell, Brian W.
Abstract: Despite the recent identification of over 40 missense heterozygous Reelin gene ( RELN ) mutations in autism spectrum disorder (ASD), none of these has been functionally characterized. Reelin is an integral signaling ligand for proper brain development and post‐natal synapse function – properties likely disrupted in ASD patients. We find that the R2290C mutation, which arose de novo in an affected ASD proband, and other analogous mutations in arginine‐amino acid‐arginine domains reduce protein secretion. Closer analysis of RELN R2290C heterozygous neurospheres reveals up‐regulation of Protein Disulfide Isomerase A1, best known as an endoplasmic reticulum‐chaperone protein, which has been linked to neuronal pathology. This effect is recapitulated in a heterozygous RELN mouse mutant that is characterized by defective Reelin secretion. These findings suggest that both a deficiency in Reelin signaling and pathologic impairment of Reelin secretion may contribute to ASD risk. Abstract : Reelin is an integral signaling ligand for proper brain development and post‐natal synapse function – properties likely disrupted in autism spectrum disorder (ASD) patients. We find that ASD‐associated de novo RELN R2290C and other arginine‐amino acid‐arginine (RXR) motif mutations impair Reelin protein secretion. R2290C heterozygous neurospheres also have augmented expression of an ER chaperone, PDIA1, a feature shared with cerebella in a heterozygous mouse model with a Reelin‐secretion deficiency.